2015
DOI: 10.2131/jts.40.365
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum and benzo[a]pyrene co-operate to induce neuronal apoptosis <i>in vitro </i>

Abstract: Toxic and harmful factors co-exist in the environment; these factors often interact to induce combined toxicity, which is the main focus of toxicological research. Furthermore, a large number of studies have shown that aluminum (Al) and benzo[a]pyrene (BaP) are neurotoxic and target the central nervous system to cause neuronal apoptosis. Because we are exposed to both Al and BaP in the air, water, food, and even medicine, the combined effects of these agents in humans must be examined. The present study examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
(40 reference statements)
0
3
1
Order By: Relevance
“…The observed decrease in cellular proliferation in the presence of drugs is expected as one of the modes of action of the drugs is inhibition of cellular growth and the killing of fast growing cells [ 112 , 113 ]. Contrary to our results, BaP has been found to induce apoptosis in several cells including neurons and hepatocytes [ 114 , 115 , 116 , 117 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The observed decrease in cellular proliferation in the presence of drugs is expected as one of the modes of action of the drugs is inhibition of cellular growth and the killing of fast growing cells [ 112 , 113 ]. Contrary to our results, BaP has been found to induce apoptosis in several cells including neurons and hepatocytes [ 114 , 115 , 116 , 117 ].…”
Section: Discussioncontrasting
confidence: 99%
“…and metalloids. Such studies published these past three years in the Journal of Toxicological Sciences investigated the toxicity of many types of metals, including cadmium (Ohtani et al, 2013;Miura et al, 2013;Baba et al, 2014;Du et al, 2014;Park et al, 2015;Lukkhananan et al, 2015), mercury (Yoshida et al, 2013;Kim et al, 2014), methylmercury (Hwang et al, 2013a(Hwang et al, , 2013bIwai-Shimada et al, 2013;Chang et al, 2013;Hirooka et al, 2013;Kim et al, 2013;Watanabe et al, 2013;Shao et al, 2015;Toyama et al, 2015), aluminum (Zhang et al, 2013;Jinzhu et al, 2015), manganese (Fujishiro et al, 2013), uranium (Lestaevel et al, 2013), arsenic (Tokumoto et al, 2013;Wang et al, 2015), arsine (Kato et al, 2014), organic bismuth (Kohri et al, 2015), chromium (Kimura et al, 2015), and tributyltin (Oyanagi et al, 2015). Although methylmercury is one of the organic-inorganic hybrid molecules (the minimum unit!…”
mentioning
confidence: 99%
“…Moreover, the results showed that the disruptive effects of nicotine on the neurotransmitters was worsened by exposure to benzo[a]pyrene, which suggests that the combined effect of both chemicals exacerbates the impact of tobacco smoke on the developing brain. Jinzhu et al [ 45 ] also established that co-exposure of aluminium and benzo[a]pyrene synergistically induced apoptosis in rat neuronal cultures.…”
Section: Discussionmentioning
confidence: 99%